DIAN (Dimentional Analysis); To Analyzing Patterns Polarization of Perception, Motivation and Preferences to Develop The Ecotourism Betawi Traditional Culinary - Untari, Dhian Tyas (Journal of Economic Development, Environment and People, 2018)
DIAN is a modification of MDS (Multidimensional Analysis), CA (Correspondence Analysis) and IPA (Important Performance Analysis). The DIAN model is formed to provide information (mapping) of GAP that occurs between stakeholders in the concept of regional development. In this paper, the implementation of DIAN will be explained in describing the GAP that occurs between Culturist, Government, Entrepreneurs and Communities to develop the Ecotourism of Betawi Traditional Culinary. The DIAN model has been patented in the Ministry of Law and Human Rights of the Republic of Indonesia and the purpose of this paper is to publish the DIAN Model more broadly. This study can be a new model in enriching knowledge and regional development